THERMO-OXIDATIVE STABILITY OF HIGH-TEMPERATURE GREASES - Zheleznyi, Leonid (Proceedings of National Aviation University (archive), 2016)
It the article is established the connection between a group hydro-carbon composition of basic petroleum oils and thermooxidative properties of high-temperature lithium complex greases. Differences in thermooxidative properties of model greases were explained. Greases on the residual oils were characterised by high anti-oxidative properties over a wide range of application temperatures and could be used as the main component of a dispersion medium of high temperature greases.